A 3D involvement comprehension model for the digital innovation fostering initiatives of the financial services industry. - Stamoulis, Dimitrios S. (Archives of Business Research, 2021)
The financial services industry word-wide is active not only in financing the innovation, but also in creating opportunities for digital innovation take-up that will ultimately lead to economic growth and entrepreneurial success. By analyzing the activities of the four major financial institutions in Greece in the area of innovation support activities, a 3D model is constructed that clearly demonstrates the strategic area that is shaped for initiatives that foster innovation in the financial services industry sector. This model is also useful as a strategic positioning tool as well as a comprehension model for those actors that would like to enter into this area and gain an understanding of the projects and activities already run by the actors in this field.